Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.3390/su10072557
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Waste Management Customer Online Value Co-Creation on Sanitation Attitude and Advocacy: A Customer-Enterprise Dyadic Perspective

Abstract: Abstract:The study aims at establishing the benefits of actively utilizing the intangible resources of solid waste management customers in designing and implementing solid waste collection services, using the social media platforms. While Ghana generates high volumes of solid waste on a daily basis, less than half of it is effectively collected and disposed of. This calls for the adoption of innovative strategies to better connect and serve customers. Adopting a marketing approach to solid waste management has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 39 publications
1
15
0
Order By: Relevance
“…Second, our findings provide a theoretical expansion on how co-creation influences customer satisfaction by confirming prior studies carried out by Frempong et al (2018). Their study revealed co-creating of value does affect positively customer satisfaction.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Second, our findings provide a theoretical expansion on how co-creation influences customer satisfaction by confirming prior studies carried out by Frempong et al (2018). Their study revealed co-creating of value does affect positively customer satisfaction.…”
Section: Discussionsupporting
confidence: 89%
“…Hunt et al (2012) postulates that community benefits and self-effect bias are the two sources of satisfaction that results out of value co-creation. Frempong et al (2018) find evidence that value co-creation is an immediate antecedent to satisfaction.…”
Section: Customer Satisfactionmentioning
confidence: 83%
“…Relational embeddedness (RE) is a core concept in the research of new economic sociology and an important tool for the study of a corporate relationship network [9]. It has a certain impact on enterprises' resource acquisition, knowledge sharing, technological innovation, and other behaviors and further affects the improvement of corporate performance and the shaping of competitive advantages [18,19]. This paper proposes that RE refers to the degree to which transport demand subjects participate in value cocreation.…”
Section: Relational Embeddedness (Re)mentioning
confidence: 99%
“…On the other hand, customers (demanders) can apply their own knowledge, skills, and experience to value creation activities, such as putting forward demands, purchasing, and using products or services, so as to achieve rapid demand satisfaction and better experience [2]. Suppliers and demanders are involved in each other's value creation, so as to realize the integration and collaboration of both sides in resources, capabilities, and knowledge, so as to better meet customer needs and improve enterprise performance [16,19]. The main activity involved in platform value cocreation is resource integration [24,25].…”
Section: Value Cocreation (Vcc)mentioning
confidence: 99%
See 1 more Smart Citation